The role of learning environment in teaching English in the context of inclusive education - Moiseeva, L.V.; Assanova, D.N.; Shalbayeva, D.Kh. (KSU Publ., 2020)
The article discusses the basic principles of inclusive education in a comprehensive school for students with special educational needs at the English lesson from the perspective of their application in the educational process. The concept of «inclusive education» and its significant difference from the «integrated education», pointing to the availability/non-availability of the learning environment adaptation to students with special educational needs, have been studied as well. The application of the learning environment theory when teaching English within the inclusive education and its main components have also been examined. The study reveals English teachers’ basic needs for creating learning environment teaching techniques in the context of the inclusive education. It also defines the concept «learning environment» and its main components. The study results conducted to define the availability/non-availability of a barrier-free learning environment, in particular, in English classrooms for implementing the inclusive education principles, have been shown and analyzed. The ways to create learning environment at the English lessons, promoting a respectful assistance to disabled students when learning English, have been studied. The group training and other teaching methods, promoting the development of disabled students’ communicative and other skills while interacting with classmates in English classes, are given.
Инклюзивті білім берудегі ағылшын тілін оқытудағы білім беру ортасының рөлі
Роль образовательной среды в обучении английскому языку в условиях инклюзивного образования
Keywords: inclusive education in Kazakhstan; learning environment; integrated education; English Teaching Methodology; disabilities; mental retardation; special educational needs; teaching students with special educational needs; special methodology